Visitation report to Sultanah Bahiyah Hospital, Alor Setar, Kedah 29-30th August 2007 - Mohd Nawawi, Norwina ([s.n.], 2007)

(untitled)
The report forms part of the requirement of a brief post occupancy evaluation visit to Sultanah Bahiyah Hospital in Alor Setar, Kedah. The findngs of the visit were feedback to Shah AlAm Hsspital project development from planning, choice of structural grid, buildings finishes and quality of space.